2010
DOI: 10.1371/journal.pone.0009987
|View full text |Cite
|
Sign up to set email alerts
|

An Implantable Vascularized Protein Gel Construct That Supports Human Fetal Hepatoblast Survival and Infection by Hepatitis C Virus in Mice

Abstract: BackgroundWidely accessible small animal models suitable for the study of hepatitis C virus (HCV) in vivo are lacking, primarily because rodent hepatocytes cannot be productively infected and because human hepatocytes are not easily engrafted in immunodeficient mice.Methodology/Principal FindingsWe report here on a novel approach for human hepatocyte engraftment that involves subcutaneous implantation of primary human fetal hepatoblasts (HFH) within a vascularized rat collagen type I/human fibronectin (rCI/hFN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 78 publications
(79 reference statements)
0
8
0
Order By: Relevance
“…We have also shown that other classic primary human hepatocyte culture models – such as hepatocytes on rigid collagen, collagen gel sandwich, Matrigel spheroids, and even randomly distributed co-cultures of the same two cell types used in MPCCs – do not sustain HBV or HCV infection as robustly as MPCCs 15,28 . Other groups have developed primary human hepatocyte models that permit HBV infection 56 and, more recently, HCV infection 5759 . Nonetheless, while they do offer initial exciting results, it remains to be determined whether these models offer the stability in hepatic phenotype, reproducibility, and robustness that is routinely observed with MPCCs.…”
Section: Introductionmentioning
confidence: 99%
“…We have also shown that other classic primary human hepatocyte culture models – such as hepatocytes on rigid collagen, collagen gel sandwich, Matrigel spheroids, and even randomly distributed co-cultures of the same two cell types used in MPCCs – do not sustain HBV or HCV infection as robustly as MPCCs 15,28 . Other groups have developed primary human hepatocyte models that permit HBV infection 56 and, more recently, HCV infection 5759 . Nonetheless, while they do offer initial exciting results, it remains to be determined whether these models offer the stability in hepatic phenotype, reproducibility, and robustness that is routinely observed with MPCCs.…”
Section: Introductionmentioning
confidence: 99%
“…For several years now, the HIV/AIDS research community has used human bone marrow grafts in immuno‐deficient mice to study HIV/AIDS because HIV tropism for human cells made it impossible to study the biology of HIV infectivity in mice . More recently, and in large part because of their success, these human–mouse chimeric models have been adapted to study human responses in diabetes, sepsis and burn injury . Here we build on the development of these chimeric mouse technologies to show that human myeloid cells can be analyzed in an in vivo model of cutaneous inflammation .…”
Section: Discussionmentioning
confidence: 99%
“…For example, when the HIV/AIDS research community encountered problems modeling the disease progression in standard mouse models because of the human‐specific tropism of the HIV virus, they created chimeric mice with human CD34 + ‐HSPCs grafts to study infection . Since then, the wider availability of these models has led to their widespread use to study other human diseases including diabetes, sepsis, and burn injury …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, long-term cultures of primary human fetal hepatocytes were developed by plating a hepatic cell mixture at low density, allowing outgrowth of nonparenchymal cells and formation of hepatic islands that were subsequently cultured under DMSO-containing conditions to maintain characteristic hepatocytic features; these cultures were susceptible to HBV infection for up to 10 weeks in culture (151). In 3D engineered tissues, Bcl-2-transduced HUVECs have been used to modulate fetal hepatocyte phenotype and permit HCV replication (151a). …”
Section: Hepatotropic Virus Infection In Models With Emergent Propertiesmentioning
confidence: 99%